The Component Timed-Up-and-Go test: the utility and psychometric properties of using a mobile application to determine prosthetic mobility in people with lower limb amputations. (March 2018) - Clemens, Sheila M; Gailey, Robert S; Bennett, Christopher L; Pasquina, Paul F; Kirk-Sanchez, Neva J; Gaunaurd, Ignacio A
Objective: Using a custom mobile application to evaluate the reliability and validity of the Component Timed-Up-and-Go test to assess prosthetic mobility in people with lower limb amputation. Design: Cross-sectional design. Setting: National conference for people with limb loss. Subjects: A total of 118 people with non-vascular cause of lower limb amputation participated. Subjects had a mean age of 48 (±13.7) years and were an average of 10 years post amputation. Of them, 54% ( n  = 64) of subjects were male. Intervention: None. Main measure: The Component Timed-Up-and-Go was administered using a mobile iPad application, generating a total time to complete the test and five component times capturing each subtask (sit to stand transitions, linear gait, turning) of the standard timed-up-and-go test. The outcome underwent test–retest reliability using intraclass correlation coefficients (ICCs) and convergent validity analyses through correlation with self-report measures of balance and mobility. Results: The Component Timed-Up-and-Go exhibited excellent test–retest reliability with ICCs ranging from .98 to .86 for total and component times. Evidence of discriminative validity resulted from significant differences in mean total times between people with transtibial (10.1 (SD: ±2.3)) and transfemoral (12.76 (SD: ±5.1) amputation, as well as significant differences in all five component times ( P  < .05). Convergent validity of the Component Timed-Up-and-Go was demonstrated through moderate correlations with the PLUS-M ( rs  = −.56). Conclusion: The Component Timed-Up-and-Go is a reliable and valid clinical tool for detailed assessment of prosthetic mobility in people with non-vascular lower limb amputation. The iPad application provided a means to easily record data, contributing to clinical utility.